Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3233/jad-2011-110414
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Alzheimer's Disease: A Systematic Review

Abstract: Preventing Alzheimer's disease (AD) would require knowledge about its etiology to a degree of detail not yet available. The major hurdle in understanding the disease lies in teasing out the various causes and their complex interactions. Since considerable data have accrued showing that the essential trace element selenium (Se) might play different roles in the progression of AD, we conducted a systematic review of the literature regarding Se and AD. We identified 9 placebo-controlled studies (6 were multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 266 publications
2
111
0
2
Order By: Relevance
“…A clinical picture of the disease is manifested by progressive loss of memory and speech as well as by cognition and behavioural deficits [99]. According to the classical hypothesis, the neurotoxic effect of Aβ is mediated by excessive free radical liberation and disturbances in Ca 2+ homeostasis [96,100]. An imbalance between free radical formation and efficiency of the antioxidant system is responsible for the widespread occurrence of protein and lipid oxidation, nucleic acid damage and mitochondrial abnormalities [99].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…A clinical picture of the disease is manifested by progressive loss of memory and speech as well as by cognition and behavioural deficits [99]. According to the classical hypothesis, the neurotoxic effect of Aβ is mediated by excessive free radical liberation and disturbances in Ca 2+ homeostasis [96,100]. An imbalance between free radical formation and efficiency of the antioxidant system is responsible for the widespread occurrence of protein and lipid oxidation, nucleic acid damage and mitochondrial abnormalities [99].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Finally, relationships between Alzheimer's disease and several protective elements have also been established. In this sense, it has been demonstrated that a negative correlation exists between cognitive impairment and levels of selenium, as well as the activity of different selenoproteins, in patients affected by AD [22]. Furthermore, it has been described that zinc might play a neuroprotective role against Aβ-induced cytotoxicity due to its antioxidant properties [23].…”
Section: The Biological Importance Of Metalsmentioning
confidence: 99%
“…However, the exact role of these elements in pathogenesis of AD is still unknown. Numerous authors have also demonstrated a negative correlation between cognitive impairment and levels of selenium, as well as the activity of different selenoproteins, in patients affected by AD [22]. Thus, although results from selenium analysis in brain tissue are inconclusive [24,[49][50][51], levels of this metalloid in blood serum and plasma are usually decreased [26-27, 32, 36, 52-53], which could be indicative of a protective response against oxidative stress.…”
Section: The Biological Importance Of Metalsmentioning
confidence: 99%
“…It could provide the neuroprotection against traumatic brain injury and could modulate the oxidative stress and cytokine values [101][102][103] . It's essential role has been reported in Alzheimer's and cognitive impairment [104][105][106] .…”
Section: (B) Exogenous Antioxidants In Neurodegenerative Diseasesmentioning
confidence: 99%